HIV-1 envelope glycoproteins isolated from Viremic Non-Progressor individuals are fully functional and cytopathic - Cabrera-Rodríguez, Romina (Sci Rep, 2019)
In untreated HIV-1-infected individuals, viremia is positively associated with disease progression. However, some viremic non progressors (VNPs) individuals show paradoxical high CD4(+) T cell counts. HIV-1 envelope glycoprotein complex (Env) is a major cytopathic determinant in viral replication; therefore, we have deeply characterized Env function in this rare clinical phenotype. Full-length Env clones isolated from individuals with Viral Load (VL) > 10,000 copies/mL classified as VNPs (n = 15) or rapid progressors (RPs, n = 17) were geno- and phenotypically analyzed by determining diversity, expression, CD4 binding/signaling, fusogenicity, infectivity and autophagy induction. Selected Env clones from VNPs and RPs (n = 32) showed similar expression, fusion and infection abilities. Env clones from both groups showed similar affinity for CD4 during cell-to-cell transmission and consistently induced similar levels of CD4 signaling, measured by α-tubulin acetylation. Moreover, we demonstrate for the first time that primary Env clones from VNP and RP induce autophagy in uninfected cells and that this feature correlated with fusogenic capacity but was unrelated to disease progression. In conclusion, our data suggest that Env clones from VNP individuals are fully functional. Therefore, the paradoxical CD4(+) T cell count stability coexisting with high levels of viral replication is unrelated to Env function.